Micromechanical fracture analysis of laminated glass-epoxy composite material tested by bending - Slaviša Putić; Dragoljub Ilić; Dragoljub Bekrić (Zaštita Materijala)
The object and purpose of this work is the micromechanical analysis of failures caused by mechanical tests of laminate glass-epoxy composite material in bending. The structure of glass-epoxy composite material is a glass fabric 280 g / m2, 'twill weave', width 100 cm, type - Interglas 92125 and epoxy resin type MGS L-135. Samples are shaped manual method with 35% volume fraction of fibers. Previous mechanical tests were obtained relevant data on tensile and flexural mechanical properties. By analyzing the images of fracture surfaces of larger magnification with a scanning electron microscope (SEM) will be performed micromechanical analysis that will lead to the knowledge of the mechanisms of damage and crack growth to final fracture in action bending loads.